PRODUKSI BIOETHANOL DARI BIJI BUAH NANGKA (Artocarpus heterophyllus Lam.) SECARA HIDROLISIS ENZIMATIS DENGAN PENAMBAHAN AMPAS TAHU SEBAGAI NUTRISI PADA FERMENTASI MENGUNAKAN MIKROBA Saccaromyces cerevisiae - Ana Fitriani (PROSIDING SEMINAR KIMIA, 2020)
Jackfruit seeds are one of the foods that have not been used so far. Jackfruit seeds contain carbohydrates which can be used as bioethanol. Research on the manufacture of ethanol from jackfruit seed flour (Artocarpus heterophyllus Lam.) Using Saccharomyces cerevisiae with the addition of tofu pulp as a source of nutrition for microorganisms at the time of fermentation. This research was conducted to determine nutrient concentration and fermentation time to produce optimal ethanol concentration. The hydrolysis process is carried out enzymatically using Î±-amylase at the liquefaction stage at pH (6 - 6.5) and gluco-amylase at the saccharification stage at pH (4- 5). Then carried out the fermentation process with a variation of time (6; 8 and 10) days using yeast Saccharomyces cerevisiae with a nutrient concentration of tofu pulp (0.75; 1.5 and 2.25)% (w / v). Then the distillation process on the results of the fermentation was carried out to produce the most ethanol distillate on day 8 of 14.5 mL. Keywords: Bioethanol, Jackfruit Seed (Artocarpus heterophyllus Lam.), Tofu Dregs, Fermentation